Students’ Perception in Learning the Course Mathematics in the Modern World: A Qualitative Study - Barete, Melvin; Taja-on, Evan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Mathematics fosters analytical thinking, problem-solving, and logical reasoning, essential for academic success and daily decisions. The course